Alexander D. Makatsariya is 2022 Best Author - article Editorial (Акушерство, гинекология и репродукция, 2023)
In 2022, A.D. Makatsariya, Doctor of Medical Sciences, Professor, Academician of the Russian Academy of Sciences, wasrecognized as the Best Author of the Sechenov University. The diploma and the award were solemnly presented by P.V. Glybochko,Doctor of Medical Sciences, Professor, Academician of the Russian Academy of Sciences, Rector of the Sechenov University.